If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 23 Reorder the terms: 6 + 5x = 23 Solving 6 + 5x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 23 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 23 + -6 5x = 23 + -6 Combine like terms: 23 + -6 = 17 5x = 17 Divide each side by '5'. x = 3.4 Simplifying x = 3.4
| 3x=2x+25 | | 3.3x=2.2x+5.5 | | x/(-2)=7 | | -8t=34 | | (c^3+2c^2d+cd^2)=0 | | X-8=40 | | 13-x=-3 | | 5-4x+5x=6x-12 | | z+1=-17 | | 4x^2+2x+7=0 | | 0.3x+0.4(10)=0.2(x+20) | | x-54=-7 | | 4x=s+5x | | x/10+2=18 | | 2x=5x-3y | | 2(3.14)=5x-3y | | 5.8+1.3n=2.29 | | (y-1)+y=11 | | 6x^2+6x+6=14x+14 | | 1x-9=14 | | -(68c+38d+8)= | | -6x-y+3xy=18 | | x^2-3.5X+3.0625=1.0625 | | -6x-y+3xy-18=0 | | 3d+4=2+3d+0.5 | | 7x-(4x+2)= | | 2a+6=3 | | 22=2x-8 | | 6-3(6)= | | w-6-12=-8 | | 3a+7b=23 | | 1x=7 |